(untitled) (International Seven Journal of Multidisciplinary, 2025)
There is a wide range of concerns surrounding the effects of artificial intelligence assistants on educational processes; therefore, this article is part of an analysis of the implications of technological assistants in educational practice. To this end, the origins of artificial intelligence are outlined, as well as the challenges and implications of teaching discourse in a practical setting such as education. We then proceed to reflect on the transformations that will need to occur in the classroom to outline the classrooms of the present and the challenges enunciated for the future of education. Together, theoretical and reflective elements regarding teaching practice are outlined. We then begin with a literature review that grounds the study process from a theoretical perspective. We then clarify the essential themes that comprise current teaching practice to glimpse the changes that will need to occur in the teaching profession to address these challenges.